2010
DOI: 10.1007/s00262-010-0927-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of circulating regulatory T cells in patients with metastatic prostate cancer pre- versus post-vaccination

Abstract: We have previously shown that the suppressive function of regulatory T cells (Tregs) from peripheral blood mononuclear cells (PBMCs) is enhanced in patients with prostate cancer when compared with healthy individuals. Two phase II studies using the PSA-TRICOM vaccine in patients with metastatic castration-resistant prostate cancer (mCRPC) showed evidence of patient benefit in terms of enhanced survival. The Halabi nomogram has been used to predict survival (HPS) of patients with mCRPC treated with conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…Tregs are crucial in maintaining peripheral tolerance to self antigens, and hence dampen effector T cell responses against many tumor antigens (31) . These suppressive cell types pose an obstacle to effective anti-tumor immunity, with both Tregs (32) and MDSC (33) being shown to affect vaccine induced immune responses. Hence, we thought it valuable to assess the frequency of these suppressive cells in the participants both pre- and post-vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs are crucial in maintaining peripheral tolerance to self antigens, and hence dampen effector T cell responses against many tumor antigens (31) . These suppressive cell types pose an obstacle to effective anti-tumor immunity, with both Tregs (32) and MDSC (33) being shown to affect vaccine induced immune responses. Hence, we thought it valuable to assess the frequency of these suppressive cells in the participants both pre- and post-vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T-cell activity was successfully blocked in mice with the monoclonal anti-CD-25 antibody daclizumab [4]. In phase II studies concerning the immunosuppressive effect of regulatory T lymphocytes, a survival advantage was registered in castration-resistant prostate cancer [14,15]. Only sipuleucel-T (ProvengeÔ) is approved for the treatment of castrationresistant prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…These initiate the production of interleukin, interferon and tumour necrosis factor-, and stimulate the proliferation of cytotoxic cells and lymphokine-activated killer cells, as well as the cytotoxicity of macrophages. IL-2 is referred to as a T-cell growth factor [12][13][14][15]. The regulatory T lymphocytes CD8 + and CD25 + , activated by IL-2, are found in prostate cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that FOXP3 + T-regs appear to relatively decrease postbooster in normal responders, which was shown upon hepatitis A vaccination in healthy donors and in breast cancer patients receiving a Her-2/neu vaccine (34). Also, the application of a prostate cancer vaccine resulted in lower T-reg numbers postvaccination in investigated patients; additionally reduced T-reg activity postbooster correlated positively with the overall survival of these patients (35). The decrease of T-regs as percentage of CD4 T cells postbooster is most likely not in absolute numbers, but rather a result of Ag-specific T-effector cell expansion postbooster.…”
Section: Discussionmentioning
confidence: 99%